How early olfactory experiences influence brain development in mice - Nishizumi, Hirofumi (Frontiers in Neural Circuits, 2025)
Mammalian sensory systems develop through both activity-dependent and activity-independent processes. While the foundational neural circuits are encoded by genetics, their refinement depends on activity-driven mechanisms. During the neonatal critical period - a specific developmental phase - sensory circuits adapt and mature in response to environmental stimuli. Initially, this plasticity is reversible, but over time, it becomes permanent. Lack of adequate stimulation during this phase can lead to impaired neural function, highlighting the importance of sensory input for optimal system development. In mice, olfactory neural circuits are first established largely through genetic programming. However, early exposure to environmental odors is crucial in shaping these circuits, affecting both odor perception and social behaviors. This review explores recent findings on the development of olfactory circuits in mice and their impact on behavior.